2011
DOI: 10.1371/journal.pone.0021838
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Occurrence and Severity of Pneumonia Due to Pandemic H1N1 2009 by Early Oseltamivir Administration: A Retrospective Study in Mexico

Abstract: BackgroundAnti-viral treatment has been used to treat severe or progressive illness due to pandemic H1N1 2009. A main cause of severe illness in pandemic H1N1 2009 is viral pneumonia; however, it is unclear how effective antiviral treatment is against pneumonia when administered >48 hours after symptom onset. Therefore, we aimed to determine how time from symptom onset to antiviral administration affected the effectiveness of antiviral treatment against pneumonia due to pandemic (H1N1) 2009.Methods/Principal F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
38
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 14 publications
6
38
1
Order By: Relevance
“…Limitations aside, this analysis demonstrates an association between NAI supply and H1N1 mortality during the 2009 influenza pandemic at an ecological level consistent with other findings on the individual level 3, 10, 14. This effect does not seem large on a population level and equates to a drop in mortality in the Americas from the observed 1·18 per 100 000 to 1·16 per 100 000 for a 10% increase kg of oseltamivir/100 000.…”
Section: Discussionsupporting
confidence: 86%
“…Limitations aside, this analysis demonstrates an association between NAI supply and H1N1 mortality during the 2009 influenza pandemic at an ecological level consistent with other findings on the individual level 3, 10, 14. This effect does not seem large on a population level and equates to a drop in mortality in the Americas from the observed 1·18 per 100 000 to 1·16 per 100 000 for a 10% increase kg of oseltamivir/100 000.…”
Section: Discussionsupporting
confidence: 86%
“…Individual observational studies during the 2009–2010 pandemic suggest a possible benefit of NAIs in reducing pneumonia incidence, but are limited by small sample sizes 13, 14, 15, 16. A meta‐analysis of 2009–2010 pandemic data from patients hospitalised with influenza A(H1N1)pdm09 virus infection reported that early treatment with NAIs reduced the likelihood of IRP compared to late treatment by 65% 17.…”
Section: Introductionmentioning
confidence: 99%
“…However, we did not stratify illness severity as part of the study or take into consideration the possibility that late treatment may benefit severely ill patients who are hospitalised with influenza, as such treatment falls outside NICE guidance. Evidence indicates that oseltamivir (Tamiflu ® , Roche) treatment of patients hospitalised with seasonal [71][72][73] and pandemic 2009 H1N1 influenza [74][75][76][77][78][79][80] is associated with reductions in radiological pneumonia, illness severity and death. Even when administered > 48 hours after symptom onset, oseltamivir showed considerable potential for reducing pneumonia due to 2009 pandemic H1N1 virus.…”
Section: Discussionmentioning
confidence: 99%
“…Even when administered > 48 hours after symptom onset, oseltamivir showed considerable potential for reducing pneumonia due to 2009 pandemic H1N1 virus. 79 Survival benefits for H5N1 influenza have also been observed when treatment with oseltamivir was delayed up to 6 days after symptom onset. 81 l Second, the ability to diagnose influenza is dependent on the sensitivity of the test.…”
Section: Discussionmentioning
confidence: 99%